A trap for the unwary: Enforcing writs of seizure and sale against joint tenancies - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2022)
Joint tenancies are a common method of holding properties in Singapore, and yet, the issue in relation to enforcing writs of seizure and sale against a judgment debtor who owns a property on a joint tenancy with another is fraught with great legal and procedural uncertainty. This paper seeks to cut through the thicket of confusion by unpacking the various legal and procedural difficulties surrounding enforcing a judgment via a writ of seizure and sale against a judgment debtor who owns property as a joint tenant with another. Specifically, this article seeks to offer solutions to the practical difficulties of registering a writ of seizure and sale, effecting a sale in the face of a prior mortgagee’s objection and the issue of priorities in relation to the surplus of the sale proceeds.